Gendered Power Relations in the Language of Wayang Topeng Malangan in the Play Panji Dalang Patah Kuda Narawangsa, Kedungmonggo, Malang Regency - Hadzrat Maulana Muhammad Zulfikar; Pramutomo; Aris Setiawan (Universitas Airlangga, 2025)
The Wayang Topeng Malang performance titled Dhalang Patah Kuda Narawangsa is one of the unique plays staged by Padepokan Asmarabangun, alongside Ronggeng Rara Jiwa – Rara Tangis. This play presents peculiarities surrounding gender fluidity, which influence the power relations among characters through the dialogues delivered. To further explore this notion, this study employs Connell’s theory of gender hegemony as the primary analytical tool, and Peirce’s semiotics theory as a supporting framework to examine the language used through discourse analysis. In doing so, it contributes to the field of Linguistic Anthropology. This study aims to document the Wayang Topeng Malangan performance and investigate the systems and forms of power embedded within it through linguistic practices. The research shows that the language used constructs a system of masculine power when interacting with characters that present as either masculine or feminine. This practice creates hegemony by rejecting heterogeneous expressions of masculinity and their constitutive elements. Thus, gendered power emerges through linguistic choices—particularly those that convey emotional detachment and aggressiveness. Gendered power relations in the form of hegemony are present in both private spaces, such as the household, and public spaces, such as governance. The more frequent the enactment of power in these spaces, the greater the scale of masculinity that is produced.